Model pendampingan pada mahasiswa difabel untuk menunjang keberhasilan akademik - Muallifah Muallifah; Elok Faiz Fatma El-Fahmi; Fuji Astutik (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2022)
Abstract: Students with disabilities have the right to get a quality education up to university, students can plan their careers and achieve academic success based on their potential. However, the condition of students with disabilities who have difficulty carrying out activities independently, requires assistance from the surrounding environment, including in conducting the lecture process. This study aims to explain the importance of mentoring and find an effective mentoring model for students with disabilities in carrying out academic activities on campus and achieving academic success. The research method used is qualitative research with a phenomenological approach. The subjects of this study were 5 disabled students with various disability conditions, namely quadriplegic, deaf, and speech impaired as well as assisted by several accompanying students. The results of the study showed that assistance to students with disabilities is essential for supporting the achievement of student academic success. The mentoring model that is expected to support the academic success of students with disabilities are (a) have sign language competence, (b) assistants can act as motivators, (c) assistants act as counselors, and (d) can provide psychological support for students with disabilities. These various mentoring models are expected to support the effectiveness of lectures and the achievement of academic success for students with disabilities.Keywords: students with disabilities; mentoring models; academic successAbstrak: Mahasiswa difabel memiliki Hak untuk mendapatkan pendidikan berkualitas sampai tingkat universitas, mahasiswa dapat merencanakan karir mereka dan memperoleh kesuksesan akademik berdasarkan potensi mereka. Akan tetapi, kondisi mahasiswa difabel yang memiliki kesulitan melakukan aktivitas sehari-hari secara mandiri, membutuhkan bantuan dari lingkungan sekitarnya, termasuk dalam proses pembelajaran. Tujuan dari penelitian ini adalah untuk menjelaskan pentingnya mentoring dan menemukan model mentoring yang efektif untuk mahasiswa difabel dalam menunjang aktifitas akademis di kampus dan meraih kesuksesan akademik. Metode penelitian ini menggunakan pendekatan kualitatif dengan teknik fenomenologis. Subjek dalam penelitian ini adalah 5 mahasiswa difabel dengan berbagai macam kondisi disabilitas, seperti lumpuh, tuli, dan gangguan bicara yang diasisteni oleh sejumlah mahasiswa pendamping. Hasil dari penelitian ini menunjukkan bahwa asistensi kepada mahasiswa difabel sangatlah penting dalam mendukung perolehan kesuksesan mahasiswa. Kompetensi mentor yang diharapkan untuk mensupport kesuksesan akademik mahasiswa dengan disabilitas adalah: a) memiliki kompetensi bahasa isyarat, b) asisten dapat juga bertindak sebagai mentor, c) asisten dapat bertindak sebagai konselor, d) bisa menyediakan dukungan psikologis terhadap mahasiswa difabel. Berdasarkan berbagai macam kompetensi tersebut, diharapkan dapat mendukung efektifitas pembelajaran dan kesuksesan akademik bagi mahasiswa difabel.Kata Kunci: mahasiswa difabel; model pendampingan; keberhasilan akademik